Evaluating a multicomponent social behaviour change communication strategy to reduce intimate partner violence among married couples: study protocol for a cluster randomized trial in Nepal - Cari Jo Clark; Rachael A. Spencer; Binita Shrestha; Gemma Ferguson; J. Michael Oakes; Jhumka Gupta (BMC, 2017)
Abstract Background Intimate partner violence (IPV) is a significant public health issue that affects 1 in 3 women globally and a similarly large number of women in Nepal. Over the past decade, important policy and programmatic steps have been taken to address violence against women in Nepal. There remains a dearth of evidence on the effectiveness of primary violence prevention strategies. The Change Starts at Home study begins to fill this gap by utilizing a multi-component social behaviour change communication (SBCC) strategy involving a radio drama and community mobilization to shift attitudes, norms and behaviours that underpin IPV perpetration in Nepal. Methods/Design The study uses a concurrent mixed-methods design. The quantitative aspect of the evaluation is a pair-matched, repeated cross-sectional 2-armed, single-blinded cluster trial (RCT: N = 36 clusters, 1440 individuals), comparing a social behaviour change communication (SBCC) strategy to radio programming alone for its impact on physical and / or sexual IPV at the end of programming (12 months' post-baseline) and 6-months post the cessation of project activities (18-months post baseline). The qualitative aspects of the design include several longitudinal approaches to understand the impact of the intervention and to examine mechanisms of change including in-depth interviews with participants (N = 18 couples), and focus group discussions with community leaders (N = 3 groups), and family members of participants (N = 12 groups). Treatment effects will be estimated with generalized logistic mixed models specified to compare differences in primary outcome from baseline to 12-month follow-up, and baseline to 18-months follow-up in accordance with intention-to-treat principles. Discussion The study rigorously evaluates the effectiveness of a promising strategy to prevent IPV. The results of the trial will be immediately useful for governmental, nongovernmental, and donor funded programs targeting partner violence or social norms that underpin it. Findings of the study will also contribute to global knowledge on the effectiveness of media and community engagement as a primary prevention strategy for IPV. Trial registration Trial was registered in clinicaltrials.gov, NCT02942433 , 10/13/2016, retrospectively registered.